2005
DOI: 10.1111/j.1439-0507.2005.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance invasiver Fadenpilzmykosen in lungentransplantierten Patienten: Effekt antimykotischer Prophylaxe mit Itraconazol und Voriconazol

Abstract: Between January 2002 and December 2003 all 157 patients (pts) that underwent lung transplantation (LTx) at our institution were prospectively screened for invasive aspergillosis (IA) during their perioperative hospital stay. Patients were regarded as IA positive, if they met the EORTC criteria for 'probable' or 'proven' IA. Records of pts were screened retrospectively for antimycotic prophylaxis. Eight of the 157 pts developed 'probable' or 'proven' IA (5.1%) within 17 +/- 10 days after LTx. This was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…On the one hand, many patients received antifungal treatment although we found that the criteria were uncertain for IA. On the other hand, antifungal drugs are used for prophylaxis, especially in transplanted patients [4]. Obviously clinicians are often uncertain about the indication for antimycotic therapy or aim to prevent colonization in the first place [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, many patients received antifungal treatment although we found that the criteria were uncertain for IA. On the other hand, antifungal drugs are used for prophylaxis, especially in transplanted patients [4]. Obviously clinicians are often uncertain about the indication for antimycotic therapy or aim to prevent colonization in the first place [16].…”
Section: Discussionmentioning
confidence: 99%
“…are widely found in the environment, water, soil and in decomposing plants, spores can be easily inhaled and may then cause invasive pulmonary disease. The IA incidence in organ transplant recipients may be as high as 5%; mortality rates of up to 80% have been reported [4]. Antifungal therapy is expensive and adverse effects can be severe [5].…”
Section: Introductionmentioning
confidence: 99%
“…Post-transplantation single isolation (9.9%) and colonization (5.8%) by non-Aspergillus molds were common findings, as has been described (range 14-23.6%) (7,8). Of note, all but 1 episode resolved, with only 1 subsequent case of invasive infection (1 Scopulariopsis).…”
Section: Discussionmentioning
confidence: 59%
“…The prevalence of Penicillium species and dematiaceous molds was high, mainly in sputum and tracheal aspirate. Detection of these molds (with the notable exception of Penicllium marneffei) possibly corresponded to normal contamination of laboratory samples, a single isolation, or respiratory tract colonization (8). Despite the high percentage of positive specimens, only 1 subsequent case of invasive disease (ulcerative tracheobronchitis) was caused by Penicillium species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation